Study guides

☆☆

Q: X minus 2 divided by 3x plus 9 times 2x plus 6 divided by 2x minus 4?

Write your answer...

Submit

Related questions

That depends on whether or not 2x is a plus or a minus

The answer to x4+x3-14x2+4x+6 divided by x-3 is x3+4x2-2x-2

the answer is y minus 10 divided by 2.

Numerator = (x + 4)*(x + 3) Denominator = (2x - 1)*(x + 3) Calcelling out the common factor, (x + 3), the answer is (x + 4) divided by (2x - 1) provided x â‰ 0.5

4x2 + 6x - 3 (with no remainder)

X=27

2 times a number minus 17 plus 20 times a number minus 9 is the same as 2x - 17 + 20x - 9 = 22x - 26

After long division, (2x2-5x+5)/(x-2) = 2x-1+3/(x-2).

7x2 -4x -5x2 +2x = 2x2 -2x

[ (x - 4) / 15 ] / [(2x + 13) / 15] = (x - 4) / (2x + 13)

-x2+2x

-2x -11y - 13

2x+7x-10=4x+3-2x 9x-10=2x+3 7x=13 x=13/7ans

x + 1

2x^3 - 3x^2 + 4x - 3

5x lolzz 8)

f(x)= (x-7) /(-2x+7)(2x+5) set -2x+7=0 -2x=-7 x=7/2 set 2x+5=0 2x=-5 x=-5/2 x=7/2 and x=-5/2 are vertical asymptotes.

6x plus 3y minus 2x plus 5y equals 4x plus 8y.

2x + 10x - 6 = 12x - 6

This simplifies to 3x-6+4y.

(y-2) (x+4)

ㅗㅓㅕㅗType your answer here...

Assuming there are no parentheses:2 times X - 1 + 4X - 6 + 2X =2X - 1 + 4X - 6 + 2X =2X + 4X + 2X - 1 - 6 =8X - 1 - 6 =8X - 7

x - 2 = 0 if x = 2 So put x = 2 into 3x3 - 2x + 2 ie 24 - 4 + 2 = 22

(3x4 + 2x3 - x2 - x - 6)/(x2 + 1)= 3x2 + 2x - 4 + (-3x - 2)/(x2 + 1)= 3x2 + 2x - 4 - (3x + 2)/(x2 + 1)where the quotient is 3x2 + 2x - 4 and the remainder is -(3x + 2).